Overcoming Barriers to the Market Access of Biosimilars in the European Union: The Case of Biosimilar Monoclonal Antibodies - Moorkens, Evelien; Jonker-Exler, Clara; Huys, Isabelle; Declerck, Paul; Simoens, Steven; Vulto, Arnold G. (Frontiers in Pharmacology, 2016)
Background: In 2014, six of the top ten blockbuster medicines were monoclonal antibodies. This multibillion-dollar market with expiring patents is the main driver for the development of biosimilar mAbs. With the ever-increasing cost of healthcare and the economic pressure to reduce or sustain healthcare expenses, biosimilars could be instrumental in reducing costs for medication and increasing patient access to treatment. Objectives: The aim of this study is to identify and describe the barriers to market access of biosimilar mAbs in the European Union and to analyze how these barriers could be overcome. Methods: A narrative literature review was carried out using the databases PubMed, Embase and EconLit. Studies were published in English or Dutch. Additionally, the reference list of the articles was checked for relevant studies. Articles and conference papers known to the authors were included as well. Articles were also identified by searching on the website of the Generics and Biosimilars Initiative (GaBI) journal. Results: Six barriers were identified based on available literature: The manufacturing process, the regulatory process, intellectual property rights, lack of incentive, the impossibility of substitution, and the innovator’s reach. These six barriers are presented as a possible framework to study the market access of biosimilar mAbs. Based on the literature search, recommendations can be made to overcome these barriers: i) invest initially in advanced production processes with the help of single-use technology, experience or outsourcing ii) gain experience with the regulatory process and establish alignment between stakeholders iii) limit patent litigation, eliminate evergreening benefits, build out further the unitary patent and unified patent litigation system within the EU iv) create demand-side policies, disseminate objective information v) change attitude towards biosimilar switching/substitution, starting with physician and patient education vi) differentiate the biosimilar by service offerings, use an appropriate comparator in cost-effectiveness analyses. Conclusions: Barriers to the market access of biosimilar mAbs could be reduced when more transparency and communication/education is used in all steps towards market access in order to increase the trust in biosimilar mAbs by all stakeholders. Only then biosimilar mAbs will be able to fully capture their cost saving potential.